Gambaran Kejadian Kehamilan Ektopik Terganggu - Ni Luh Sri Aravianti; Made Widhi Gunapria Darmapatni; Ni Ketut Somoyani (Oksitosin : Jurnal Ilmiah Kebidanan, 2022)
Ectopic pregnancies occur in 19,7 cases out of 1000 pregnancies, and is the leading cause of maternal death in the first trimester. Risk factors for disrupted ectopic pregnancy include age, gravidity, medical history, past obstetric history, and history of contraception. The purpose of this study was to describe the incidence of disrupted ectopic pregnancy at the Wangaya Regional General Hospital, Denpasar City. This type of study was descriptive with a cross sectional approach. The results of this study are the incidence of disrupted ectopic pregnancy occurred at an average age of 27.65 years, and the most at the age of 20-35 years, multigravida, without a history of sexually transmitted infections and pelvic inflammatory disease, without a history of disrupted ectopic pregnancy, abortion, caesarean section, and tubal surgery, and no history of contraception. The study suggest that pregnant women of productive age and multigravida to carry out more routine antenatal care and carry out ultrasound at least once in early pregnancy. In future study, it is recommended to use primary data. Keywords: Disrupted ectopic pregnancy, Age, Gravidity, Medical history, Past Obstetrics History.